PENGEMBANGAN VIDEO INTERAKTIF UNTUK PENANGANAN HENTI JANTUNG SAAT OLAHRAGA - Alhamid, Fahira; Paputungan, Irving Vitra; Asyhar, Alfian N (STKIP PGRI Situbondo, 2025)
Exercise is widely recognized by both the public and experts as a key contributor to improved health. However, reality shows that cases of sudden death are sometimes reported among individuals who engage in regular exercise, either during or shortly after physical activity. Sudden cardiac arrest (SCA) is a condition characterized by the abrupt cessation of the heart's activity due to a disruption in the electrical impulses within the heart, resulting in impaired blood-pumping functions. Prompt response and understanding of emergency procedures, including the use of an Automated External Defibrillator (AED), can often be the deciding factor between life and death. Therefore, fostering better awareness and preparedness among individuals engaged in sports activities is essential to create a safer and more emergency-ready environment. The development of interactive videos has been identified as an effective educational tool to disseminate relevant information and enhance community readiness in addressing cardiac emergencies. This study employs the ADDIE method. Based on the research and testing of the interactive video on cardiac arrest management during exercise, it can be concluded that the video is highly effective in conveying information to the audience. Aspects such as video relevance, message clarity, content alignment, visual quality, and professionalism received high scores, demonstrating the video’s success in achieving its purpose as an educational medium.